Leprosy in Birmingham–a review. Issue 696 (October 1983) - Ellis, C. J.
Abstract : Twenty-three men and seven women from the West Midlands conurbation (population 2.7 million) have been investigated and treated for leprosy since 1970. The clinical features of the patients at presentation are described with an account of treatment given and the outcome. The pattern of this disease in Britain is different from that seen in the U.S.A. and poses little threat to public health. The disease can be cured by chemotherapy but neuropathy is unlikely to recover if it is a presenting symptom. The diagnosis of leprosy should be considered in all patients who have lived in an endemic area who present with disorders of peripheral nerves or skin. Early diagnosis is essential to minimize nerve damage and resulting deformity.